Analisis Kesulitan Siswa Kelas V pada Operasi Hitung Penjumlahan dan Pengurangan Bilangan Ratusan di Madrasah Ibtidaiyah - Muhammad Nasir; Wahyu Henky, Irawan; Abdussakir, Abdussakir (Pendidikan Matematika FKIP Universitas Mataram, 2025)
Learning mathematics at the basic education level is not easy, many challenges and obstacles arise to ensure that students really understand the addition and subtraction material well during learning activities. The objectives of this study are: 1) Identify the forms of student learning difficulties in understanding the concepts and procedures of addition and subtraction of Hundreds, 2) Describe the learning methods used by teachers in learning mathematics. 3) Analyzing the factors that cause low student motivation in learning mathematics. This research used a descriptive qualitative approach. The subjects of this study were 22 students of class V-B MI Roudlotul Uqul as observation subjects during learning activities, and 2 students as test subjects. The results showed that the form of difficulty experienced by students in performing arithmetic operations was the occurrence of misconceptions on the concept of place value, not understanding the concept of saving and borrowing. The factors that cause students' learning difficulties are internal factors, which include students' physical, psychological, and intellectual conditions, and external factors, which include teachers' teaching methods, learning environment, and social factors.